The role of Phosphodiesterase-1 and its natural product inhibitors in Alzheimer’s disease: A review - Ahmad, Nazir; Lesa, Kaisun Nesa; Sudarmanto, Ari; Fakhrudin, Nanang; Ikawati, Zullies (Frontiers in Pharmacology, 2022)
Phosphodiesterase-1 (PDE1) is a versatile enzyme that has surprisingly received considerable attention as a possible therapeutic target in Alzheimer’s disease (AD) because it maintains the homeostasis of 3ʹ,5ʹ-cyclic adenosine monophosphate (cAMP) and 3ʹ,5ʹ-cyclic guanosine monophosphate (cGMP) in the brain. 3ʹ,5ʹ-cyclic adenosine monophosphate and 3ʹ,5ʹ-cyclic guanosine monophosphate are the two key second messengers that regulate a broad range of intracellular processes and neurocognitive functions, specifically memory and cognition, associated with Alzheimer’s disease. However, the lack of available selective drugs on the market poses challenges to identifying the beneficial effects of natural products. The present review focuses on Phosphodiesterase-1 and its isoforms, splicing variants, location, distribution, and function; the role of Phosphodiesterase-1 inhibitors in Alzheimer’s disease; and the use of vinpocetine and natural products as specific Phosphodiesterase-1 inhibitors. Moreover, it aims to provide ongoing updates, identify research gaps, and present future perspectives. This review indicates the potential role of Phosphodiesterase-1 inhibitors in the treatment of neurodegenerative disorders, such as Alzheimer’s disease. Certain clinical trials on the alleviation of Alzheimer’s disease in patients are still in progress. Among de novo outcomes, the employment of Phosphodiesterase-1 inhibitors to treat Alzheimer’s disease is an important advancement given the absence of particular therapies in the pipeline for this highly prevalent disease. To sum up, Phosphodiesterase-1 inhibition has been specifically proposed as a critical therapeutic approach for Alzheimer’s disease. This study provides a comprehensive review on the biological and pharmacological aspects of Phosphodiesterase-1, its role on the Alzheimer’s diseases and its significance as Alzheimer’s disease therapeutic target in drug discovery from natural products. This review will help clinical trials and scientific research exploring new entities for the treatment and prevention of Alzheimer’s disease.